(untitled) (Revista Ciencia Agraria, 2023)
Objective: to determine the ecological footprint of the students of the public university of Huacho, Peru. Methodology: the sample consisted of 20 students of the Professional School of Initial Education; the survey was used as a technique and the questionnaire as a data collection instrument, which was validated by expert judgment (100%) and the reliability was determined by Cronbach’s Alpha with 0.616. Results: it was evidenced that students have a high level with respect to their ecological footprint; given that, in the procedure for its estimation, the highest score obtained per student was 435 points that represents 6.0 to 7.8 hectares and the lowest score was 195 points being their ecological footprint from 4.0 to 6.0 hectares. Conclusion: the generation of the ecological footprint of initial education students is very high, this is due to the fact that they lead a lifestyle that increases their footprint, therefore, it is essential to promote sustainable habits.